Pygmalion [videorecording (DVD)] - Asquith, Anthony, 1902-1968; Howard, Leslie, 1893-1943; Hiller, Wendy, 1912-2003; Lawson, Wilfrid, 1900-1966; Lohr, Marie, 1890-1975; Sunderland, Scott; Shaw, Bernard, 1856-1950 (Criterion collection, 2000)
Professor Henry Higgins works to make a pretty flower girl into a young lady of society.